Physical Implementation of the Eight-Core Godson-3B Microprocessor - 王茹 范宝峡 杨梁 高燕萍 刘动 肖斌 王江嵋 张译夫 王宏 胡伟武 (Journal of computer science and technology, 2011)
The Godson-3B processor is a powerful processor designed for high performance servers including Dawning Servers. It offers significantly improved performance over previous Godson-3 series CPUs by incorporating eight CPU cores and vector computing units. It contains 582.6 M transistors within 300 mm2 area in 65 nm technology and is implemented in parallel with full hierarchical design flows. In Godson-3B, advanced clock distribution mechanisms including GALS （Globally Asynchronous Locally Synchronous） and clock mesh are adopted to obtain an OCV tolerable clock network. Custom-designed de-skew modules are also implemented to afford further latency balance after fabrication. The power reduction of Godson- 3B is maintained by MLMM （Multi Level Multi Mode） clock gating and multi-threshold-voltage cells substitution schemes. The highest frequency of Godson-3B is 1.05 GHz and the peak performance is 128 GFlops （double-precision） or 256 GFlops （single-precision） with 40 W power consumption.